Shifting the Battle to Social Media: The Effectiveness of Boko Haram’s Online Strategy in Terms of its Recruitment (Academic Journal of Internal Affairs, 2021)
In 2015, after Boko Haram pledged allegiance to the Islamic State of Iraq and the Levant and became the Islamic State West Africa Province, online social media’s dominance was nearly instantaneous. This paper analyzes whether Boko Haram’s use of social media results in more effective recruitment and, if so, what trends can be observed in the former that contribute to the latter. I conclude that social media plays an instrumental role in the terrorist organization’s online recruitment since Boko Haram can disseminate instant messages to large online audiences while also exercising control over their visual content. Additionally, Boko Haram’s use of social media ties into recruitment as there is a link to radicalization, religious indoctrination, and sharing its narrative. Finally, the group uses social media to depict itself as the winning entity by representing strength, unity, and taking advantage of the country’s anti-government sentiment. While online influences are undoubtedly crucial for recruitment, it must be emphasized that they are usually coupled with offline physical connections in the Nigerian context.
Keywords: Boko Haram; Nigeria; social media; recruitment